Kesiapsiagaan Pustakawan Melalui Sertifikasi Kompetensi dan Uji Kompetensi - Endang Fatmawati (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2019)
This paper provides a conceptual understanding of the differences between the librarian certification and the librarian competency test, the role of the SKKNI Library, and offers the librarian preparedness strategy. Librarians as an important component in the digital information ecosystem play a role in encouraging the transformation of knowledge-based intelligent Indonesian society. In building a digital library, it must be supported by librarians who have competence in the library field based on the SKKNI Library. The role of the SKKNI in the library sector is as a basis for regulation in increasing the competence of Indonesian librarians, as a benchmark for the performanceof librarians, as a national reference for organizing education and training, as well as competency tests in the context of librarian competency certification. The SKKNI based librarian readiness strategy is the librarian must use the SKKNI Library as a reference in developing librarians’ competenciesand careers to improve their performance and productivity. A review of the SKKNI in the field of digital ecosystem based library needs to be done to analyze the discrepancies that have been made and improve the scope of competencies that are adjusted to the development of digital technology.